INSTITUTIONAL SECURITY OF THE SOCIAL SPHERE OF UKRAINE DURING THE CONDITIONS OF WAR - Bachynska , M.V. (The actual problems of regional economy development, 2023)
The purpose of writing the article is to study the institutional support of the social sphere of Ukraine in the conditions of war. When writing the essay, general scientific and unique research methods were applied. In particular, the method of analysis and synthesis was used to study the main functions of the multidisciplinary mobile team. The main results of the functioning of the system of institutional regulation have been established, including the reliability of socio-economic support for persons with disabilities, temporarily displaced persons, etc., their involvement in the field of labor relations, the removal of social tension in the country by providing them with work. This leads to partial satisfaction of the individual needs of disabled people with various diseases at work, temporarily resettled persons, etc. To improve and harmonize the activities of social services, it is proposed to ensure the transparent functioning of institutions within all territorial levels; ensure the coordination of a multi-level system of formation and implementation of state policy in the social sphere, in fact, the formation of a new institutional model, which should provide a living set of tools taking into account decentralization and the powers of state/local authorities. The abstract-logical method was used for theoretical generalizations and the formation of conclusions. The importance of the creation and practical activity of multidisciplinary mobile teams for IDPs under martial law is justified. It is proved that the institutional support of the social sphere plays a unique role in the activities of state and non-state organizations that implement the social direction of state activity. The action of regional social centers was studied. The most significant problems of regional social centers that require immediate solution were identified, in particular: low level of wages of social protection workers; the development of "personnel hunger"; high level of workload and its nature on social security workers; a large number of regulatory and legal acts that contradict each other; insufficient level of provision of the material and technical base. To improve the activities of social services, the following are proposed: An increase in the wages of social service workers; review of the staff of social benefits from the point of view of the quality of their services; application of information technology in the activities of social services; introduction of new relevant areas of work of social services in war conditions; ensuring territorial communities; stimulation of cross-border cooperation of territorial border communities; reviewing the possibilities of collaboration of social services with the public, donor, and international organizations.the decentralization of social services; stimulation of cooperation of neighboring.